2007
DOI: 10.1007/s10338-007-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear numerical analysis of a flexible rotor equipped with squeeze couple stress fluid film journal bearings

Abstract: This study performs a dynamic analysis of a rotor supported by two squeeze couple stress fluid film journal bearings with nonlinear suspension. The numerical results show that the stability of the system varies with the non-dimensional speed ratios and the dimensionless parameter l * . It is found that the system is more stable with higher dimensionless parameter l * . Thus it can conclude that the rotor-bearing system lubricated with the couple stress fluid is more stable than that with the conventional Newto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…In 2006, C. K. Chen et al [18] proposed a non-linear model to study the dynamic behaviour of the rotor centre and bearing centre and explained that the dynamic behaviour of the system includes 2T-periodic, quasi-periodic and chaotic motions. In 2007, C. W. Chang-Jian et al [19] investigated the dynamic analysis of a rotor supported by two couple stress fluid film journal bearings with non-linear suspension. It was concluded that rotor bearing system lubricated with couple stress fluid is more stable than that with the conventional Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
“…In 2006, C. K. Chen et al [18] proposed a non-linear model to study the dynamic behaviour of the rotor centre and bearing centre and explained that the dynamic behaviour of the system includes 2T-periodic, quasi-periodic and chaotic motions. In 2007, C. W. Chang-Jian et al [19] investigated the dynamic analysis of a rotor supported by two couple stress fluid film journal bearings with non-linear suspension. It was concluded that rotor bearing system lubricated with couple stress fluid is more stable than that with the conventional Newtonian fluid.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of periodic, quasi-periodic and chaotic motions was predicted for various ranges of rotor speeds. Chang-Jian and Chen [12][13][14][15][16] presented a series of papers discussing about flexible rotor supported by journal bearings under non-linear suspension and also combined with rub-impact effect, turbulent effect and micropolar lubricant into consideration. They found very bountiful non-periodic responses occurring in rotor-bearing systems and the studies would help engineers or scientists escape undesired motions in either designing or operating rotorbearing systems.…”
mentioning
confidence: 99%